Bud activity of decapitated, nurserygrown plants of triplochiton scleroxylon in Nigeria: effect of light, temperature and humidity - Ladipo, D.O.; Leakey, R.R.B.; Grace, J. (Elsevier, 1992)
This study is a continuation of earlier work on apical dominance inTriplochiton scleroxylon K. Schum., aimed at the development of an early clonal selection test for branching habit and yield in tree improvement programmes. Decapitated plants of five to seven clones were treated with either: (i) two photon flux densities (photosynthetically active radiation at full or 10% sunlight, approximately 2000 and 200 μmol quanta m−2s−1 measured at midday on a clear day); (ii) two temperatures (ambient 30°C or 40°C in a polythene tent); (iii) two humidities (ambient=40–70% relative humidity at 30°C or with humidification=95–100% relative humidity at 28°C). Bud activity, shoot length and numbers of leaves produced following decapitation were all increased by high photon flux density and high humidity. In contrast to similar studies under glasshouse conditions in Britain, dominance was not re-established following the initial period of sprouting. The sprouting phase was similar in Nigeria and Britain. Clonal differences in bud activity were similar under different treatments, although there were minor changes in ranking. Increasing the air temperatures from 30 to 40°C resulted in leaf areas of 165 cm2 and 23 cm2, respectively. Normal polarity of lateral shoot production following decapitation was completely inverted by high temperature